2015
DOI: 10.1155/2015/474730
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon‐Enhanced Sensing: Current Status and Prospects

Abstract: By combining different plasmonic nanostructures with conventional sensing configurations, chemical/biosensors with significantly enhanced device performance can be achieved. The fast development of plasmon-assisted devices benefits from the advance of nanofabrication technology. In this review, we first briefly show the experimental configurations for testing plasmon enhanced sensing signals and then summarize the classic nanogeometries which are extensively used in sensing applications. By design, dramatic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…The wave vector of the SPP is higher than the maximum wave vector of light propagating in air. Therefore, a higher wave vector can be realized by off‐axis illumination to a metal film through a prism, which has a higher refractive index. The refractive index variation can be detected, as the wave vector of SPP is related to the environment.…”
Section: Application Case Studiesmentioning
confidence: 99%
“…The wave vector of the SPP is higher than the maximum wave vector of light propagating in air. Therefore, a higher wave vector can be realized by off‐axis illumination to a metal film through a prism, which has a higher refractive index. The refractive index variation can be detected, as the wave vector of SPP is related to the environment.…”
Section: Application Case Studiesmentioning
confidence: 99%
“…A surface plasmon resonance (SPR) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ] is formed when the incident electrons resonate with the vibration on the surface of metallic nanostructures, which has caused broad interest regarding novel applications [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Researchers have shown that plasmonic crystals [ 20 , 21 ] are essential for superlenses [ 22 , 23 ], negative refraction applications [ 24 , 25 ], and ultra-large nonlinearity devices [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The LSPR spectral position is highly dependent on the composition, size or shape of the nanoparticles, as well as the refractive index of the dielectric medium and the spacing between them (Liz-Marzán 2005; Sonnichsen et al 2005;Yamamichi et al 2009). Typical materials for plasmonic applications are noble metals, especially silver and gold; despite silver displays more intense LSPR bands than gold, the higher chemical stability of gold nanostructures has favored its preferential application for biosensing (Estevez et al 2014;Hill 2015;Li et al 2015;Lv et al 2015;Wang and Ma 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These techniques permit an accurate control of the size, shape and spatial distribution of the nanoparticles, allowing manufacturing a wide variety of two dimensional (2D) or quasi-three-dimensional (Q3D) metal nanostructures (nanoholes, nanopillars, nanocrescents, etc. ) with particular enhanced plasmonic properties suitable for biosensing (Bhushan and Matsui 2010;Graells 2007;Guillot and de la Chapelle 2012;Li et al 2015;Lv et al 2015;Zhou et al 2016). However, these techniques are expensive and the patterned regions are small, which difficult the development of applications raising at the same time the cost of potential commercial sensing devices based on those nanostructures.…”
Section: Introductionmentioning
confidence: 99%